Systematic review on how Balance Scorecard is implemented in sales decisions in transport companies - Chavez Milla, Humberto Angel; Do Nascimento Sifuentes, Fabio Ernesto; Miranda Oliveros, Eddie; Vigo Cancino, Jhonny Manfredy (LACCEI, 2025)
The purpose of this research is to evaluate how the implementation of the Balanced Scorecard (BSC), can improve sales decisions in interprovincial transport companies, accumulating opportunities for improvement in the development of their operations to provide good customer service. The BSC is a strategic management tool that helps organizations establish strategic objectives through active performance indicators. In the context of interprovincial transport companies, the BSC allows them to address operational and administrative problems that affect the quality and profitability of the service. This work investigates the impact of the BSC on sales decisions in this sector, using a Systematic Literature Review (SLR) under the PRISMA 2020 declaration. The study found that the implementation of the BSC significantly improves operational efficiency and strategic performance, highlighting its usefulness in aligning sales strategies with organizational objectives. Additionally, the BSC facilitates detailed analysis of revenues and costs, improves punctuality and customer convenience, and promotes the development of operational skills and the implementation of new technologies. In this way, the BSC contributes to more effective decision-making, increasing customer satisfaction and ensuring the long-term sustainability and success of interprovincial transport companies.